INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN HULU SUNGAI UTARA - Syahrusiyani, Hj. (LPPM Institut Pendidikan Nusantara Global, 2024)
The Community Satisfaction Index (IKM) is the result of community satisfaction survey activities in the form of numbers. Numbers are determined on a scale of 1 (one) to 4 (four). The satisfaction index is a representation of the satisfaction scale of several dimensions formed from several indicators or attribute items. The satisfaction level and index is a value given by the public to the services provided by the public service delivery unit. This research was motivated by obstacles in providing facilities, the absence of a waiting room in the circulation service, the lack of manpower, the presence of noise in the reading room area, and the lack of renewal of books. The aim of this research is to find out the level of community satisfaction with services at the North Hulu Sungai Regency Regional Drinking Water Company (PDAM) and to measure how large the Community Satisfaction Index is with Services at the North Hulu Sungai Regency Regional Drinking Water Company (PDAM). The theory used refers to PERMENPAN-RB Number 14 of 2017. The method used in this research is descriptive quantitative, with a sample size of 100 respondents. Data collection techniques in this research were by distributing questionnaires, observation, literature study and documentation. The sampling technique used is Probability Sampling. In analyzing the data using the perception value test provisions from the general guidelines for preparing the Community Satisfaction Index. The research results show that the index value obtained is 3.003 and the community satisfaction index value after conversion is 75.0075, so the service quality is